CEFR-Based Arabic Language Learning Competency - Talqis Nurdianto; Yayat Hidayat; Vicky Adetia Wulandari (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
Learning Arabic language at CEFR does not only focus on the principles of Nahwu as science or practice, but also there are other competencies that must be included in its learning. This research aimed to formulate an easy and modern Arabic learning method for non-Arabic speakers. This research was descriptive qualitative in nature with the primarily data was the study of the Common European Framework of Reference for Language (CEFR). Data analysis was carried out by document analysis on the CEFR-based Arabic learning competency and the results were presented in descriptive form. This research resulted two main competency standards in teaching Arabic based on CEFR, they were: language competence in general and communicative language competence. In this general competency there were four derivative competencies, namely: 1) declarative knowledge; 2) expertise and skills; 3) existential competence; and (4) the ability to learn. Meanwhile, the CEFR only defined communicative language competence in its three derivative competencies, namely: 1) linguistic competence; 2) sociolinguistic competence; and 3) pragmatic competence.